Isolation, sequence identification and tissue expression profile of a novel ribokinase gene (RBKS) from Chinese Banna mini-pig inbred line (BMI) - Jinlong Huo; Pei Wang; Yongwang Miao; Hailong Huo; Yangzhi Zeng; Heng Xiao (African Journal of Pig Farming, 2018)
The complete expressed sequence tag (CDS) sequence of Banna mini-pig inbred line (BMI) ribokinase gene (RBKS) was amplified using the reverse transcription-polymerase chain reaction (RT-PCR) based on the conserved sequence information of the cattle or other mammals and known highly homologous swine ESTs. This novel gene was then deposited into NCBI database and assigned to accession number JF944892. Sequence analysis revealed that the BMI RBKS encodes a protein of 323 amino acids that has high homology with the ribokinase proteins of seven species: cattle (99%), horse (99%), orangutan (99%), human (89%), monkey (89%), rat (88%) and mouse (80%). The phylogenetic tree analysis revealed that the BMI RBKS gene has a closer genetic relationship with the RBKS genes of bovine and horse than with those of orangutan, human, monkey, rat and mouse. Analysis by RT-PCR showed that BMI RBKS gene was over-expressed in ovary and lung, moderately expressed in spleen, nerve fiber, large intestine and diencephalon, weakly expressed in heart, skin, muscle, small intestine, midbrain, kidney and fat, while almost silent in other five tissues. Four microRNA target sites were predicted in the CDS of BMI RBKS mRNA for further study of this gene in the future. The 3D structure of the RBKS by homology modeling was similar to that of human ribokinase (2fv7). Our experiment will establish a foundation for further insight into this swine gene.